Leveraging Triple Helix Synergy for Boosting SME Innovation and Competitiveness: Insights from Blitar - Suwigda Agung Novandinata; Siti Azizah; Dede Aprylasari (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a vital role in the country's economy. Still, they face various challenges, including limited resources, low managerial capabilities, and a lack of access to modern technology. The triple helix approach, which involves academics, business actors, and the government, can be a solution to increase the innovation and competitiveness of MSMEs. This research examines the synergy of the triple helix in developing MSMEs, with a case study of the MSME